Odpowiedzi

2010-03-30T15:42:34+02:00
2(x+3)-5 > -2x-7
2x+6-5 > -2x-7
2x+1 > -2x-7
2x+2x > -7-1
4x > -8 | :4
x > -2


-2(x-1)+5x > 7x+12
-2x+2+5x > 7x+12
3x+2 > 7x+12
3x-7x > 12-2
-4x > 10 | :(-4)
x < -2½


0,2x+0,3 = -0,5
0,2x = -0,5-0,3
0,2x = -0,8 | *10
2x = -8 | :2
x = -4


5x+2 = 7-3x
5x+3x =7-2
8x = 5 | :8
x = ⅝


3(x-1) = 0
3x-3 = 0
3x = 0+3
3x = 3 | :3
x = 1
2010-03-30T15:43:27+02:00
A)2(x+3)-5> -2x-7
2x+6-5>-2x-7
2x+2x>-7-6+5
4x>-8/:4
x>-2

b)-2(x-1)+5x> 7x+12
-2x+1+5x>7x+12
3x-7x>12-1
-4x>11/:(-4)
x<2 i 3/4

c)0,2x+0,3=-0,5
0,2x=-0,5-0,3
0,2=-0,8/:(0,2)
x=-4

d)5x+2=7-3x
5x+3x=7-2
8x=5/:8
x=5/8

e)3(x-1)=0
3x-3=0
3x=3/:3
x=1